Musculoskeletal injuries among professional football players in Kuwait: A protocol for a cross-sectional survey - Buabbas, M.; Pearson, S.; Albannai, A.; Merza, E. (Asian Journal of Sports Medicine, 2025)
Background: Football is by far the most played sport around the globe, but it comes with a high risk of musculoskeletal (MSK) injuries that are reported to differ greatly between professional leagues from different countries. In Kuwait, there is no available injury profile data for professional football players.